Are multiple directorships beneficial in East Asia? - Lee, Kin-Wai (2013)
We posit that the beneﬁts and costs of multiple directorships are conditional on ﬁrm characteristics. We ﬁnd ﬁrm valuation is positively associated with multiple directorships in (i) ﬁrms with high advising needs and (ii) ﬁrms with high external ﬁnancing needs. These beneﬁcial eﬀects of multiple directorships are generally stronger in countries with weak shareholder rights and in ﬁrms that are widely held. However, when controlling shareholder hold high votingrights to cash-ﬂow rights, multiple directorships reduce ﬁrm valuation, especially in countries with weak shareholder rights and in closely held ﬁrms. As multiple directorships increases, cash holdings (capital expenditures) contribute less to shareholder value. The negative association between value of cash (capital expenditure) and busy boards is mitigated in ﬁrms with (i) high advising needs, (ii) high external ﬁnancing needs and (iii) less entrenched ownership structures.